Low-cost of fix-wing prototype using Zimmerman design - Mansor, Yaakob; Omar Baki, Sharudin; Mohd Noor, Ikhwan Syafiq; Mohd Tarmizi, Emma Ziezie; Abdul Aziz, Nor Azah (Semarak Ilmu Publishing, 2023)
This paper discussed the design and development of a fix-wing UAV that uses a Zimmerman parameter. To increase structural strength, a material made of expanded polypropylene and expanded polystyrene was used. Using a bagging vacuum technique for 24 hours, the structural strength procedure thoroughly combines the resin and fiber. The Zimmerman graph, generated at speeds between 50,000 and 200,000 using Reynolds Numbers (RE), was analyzed using three key variables: the coefficient of lift, drag, and the angle of attack (Alpha) of the airfoil. At 10o, the airfoil started to stall based on indicated coefficient used. The test flight is also comprised of pitch and roll flight with adequate force and little overshoot between the autopilot's requirement and the small aircraft's actual performance.